2017
DOI: 10.1155/2017/8078346
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Report on Fiber-Reinforced Lightweight Aggregate Concrete Masonry

Abstract: Masonry construction is the most widely used building method in the world. Concrete masonry is relatively low in cost due to the vast availability of aggregates used within the production process. ese aggregate materials are not always reliable for structural use. One of the principal issues associated with masonry is the brittleness of the unit. When subject to seismic loads, the brittleness of the masonry magni es. In regions with high seismic activity and unspeci ed building codes or standards, masonry hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Rico et al [9] added steel fibres into a delicate cement matrix, according to their research, in order to increase the break resistance of the LWC by the split capture process and to improve the tensile and flexural properties. The results showed that steel fibre played a connection role inside the concrete thus helping to raise the resistance of the concrete against cracks and mentioned that increased toughness is a consequence of increased fibre.…”
Section: Steel Fibres In Light-weight Concrete (Lwc)mentioning
confidence: 99%
“…Rico et al [9] added steel fibres into a delicate cement matrix, according to their research, in order to increase the break resistance of the LWC by the split capture process and to improve the tensile and flexural properties. The results showed that steel fibre played a connection role inside the concrete thus helping to raise the resistance of the concrete against cracks and mentioned that increased toughness is a consequence of increased fibre.…”
Section: Steel Fibres In Light-weight Concrete (Lwc)mentioning
confidence: 99%
“…This is the unbranded residue that happens when the coal is finely ground at or above 75 percent and then removed from the hot area. Fly-ash is composed of 10-40% non-fuel impurities (for example, clay, shale, quartz, feldspar, dolomite, Silestone), depending on the source and grade, [11,12]. Fly Ash is non-fuel flue gas impurities after the complete combustion of high furnace temperatures of volatile and carbon flows.…”
Section: Coal Fired Fly Ashmentioning
confidence: 99%
“…As ash of fly, mechanical and electro-static connectors are used to manage the mentioned flue gas stream, while the denser, unbranded material flows to the base of the stove and is mainly called ash of fly. At present, it is estimated that worldwide fly ash production amounts to 600 million tons [11,12]. Ashes as fresh concrete characteristics, such as quality, size, shape, strength, and color, depend primarily on collecting new concrete and temperature of carbon burning [11][12][13].…”
Section: Coal Fired Fly Ashmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical application consists of textile reinforced mortars in which fibre filaments act in place of steel rebars (see Section 2 and [4][5][6]). The actual result can take the form of efficient technical solutions that are suitable especially for existing (and often historical) buildings needing massive, structural retrofit interventions, especially in regions with high seismic hazards ( [7][8][9][10]).…”
Section: Introductionmentioning
confidence: 99%